FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI BERULANG - Hermansyah, Hermansyah; Semmagga, Nuraeni; Nirwan, Nirwan; Sari, Rafika (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Hypertension is a medical condition characterized by increased blood pressure in the arteries, where systolic pressure reaches or exceeds 140 mmHg and diastolic pressure reaches or exceeds 90 mmHg. The purpose of the study was to determine the factors associated with the incidence of recurrent hypertension. The research design used in this study was cross sectional. The research was conducted at the Manipi Health Center in July 2024. The population in this study were hypertensive patients who had visited the Manipi Health Center, West Sinjai District as many as 1535 people. The research sample amounted to 95 respondents. The sampling technique used in this study was purposive sampling. Data analysis was done univariate and bivariate. The results showed there was a relationship between sodium intake (p value: 0.022) and stress (p value: 0.000) on the incidence of recurrent hypertension. It is recommended for hypertensive patients to avoid factors associated with an increase in blood pressure in this study by improving sleep quality, avoiding stress and reducing sodium intake.Keywords: Sodium Intake, Hypertension, Stress